2003
DOI: 10.1093/emboj/cdg581
|View full text |Cite
|
Sign up to set email alerts
|

On the role of the two extracytoplasmic substrate-binding domains in the ABC transporter OpuA

Abstract: Members of two transporter families of the ATP-binding cassette (ABC) superfamily use two or even four extracytoplasmic substrate-binding domains (SBDs) for transport. We report on the role of the two SBDs in the translocation cycle of the ABC transporter OpuA from Lactococcus lactis. Heterooligomeric OpuA complexes with only one SBD or one functional and one non-functional SBD (inactivated by covalent linkage of a substrate mimic) have been constructed, and the substrate binding and transport kinetics of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(68 citation statements)
references
References 86 publications
3
65
0
Order By: Relevance
“…This finding is reminiscent of type I ABC importers with one or two solute-binding domains fused to one TMD (26). The analysis of such a transporter, the OpuA complex of Lactococcus lactis, revealed that two SBPs cooperatively interact but one is sufficient for transport (27).…”
Section: Discussionmentioning
confidence: 94%
“…This finding is reminiscent of type I ABC importers with one or two solute-binding domains fused to one TMD (26). The analysis of such a transporter, the OpuA complex of Lactococcus lactis, revealed that two SBPs cooperatively interact but one is sufficient for transport (27).…”
Section: Discussionmentioning
confidence: 94%
“…14 C]glycine betaine to a final concentration of 51 M (more than 10-fold above the K m for transport and K D for binding) (40). At given time intervals, 26-l samples were taken and diluted with 2 ml of ice-cold isotonic assay buffer.…”
Section: Methodsmentioning
confidence: 99%
“…Membrane vesicles of the L. lactis Opu401/pNZOpuA derivative were isolated as described (13), and fused 1:10 with preformed liposomes, composed of dioleoyl-phosphatidylethanolamine (DOPE), dioleoyl-phosphatidylglycerol (DOPG), and dioleoyl-phosphatidylcholine (DOPC). The hybrid membranes were obtained by two freeze/thaw cycles, followed by extrusion through a polycarbonate filter (200 nm pore size); for details on the preparation of liposomes and the freeze-thaw-extrusion steps, we refer to Geertsma et al (14).…”
Section: Synthesis Of Hybrid Membranesmentioning
confidence: 99%
“…For osmotically activated transport, the hybrid membranes were diluted to a lipid concentration of 4.5-12 mg/ml into assay buffer (90 mM potassium P i , pH 7.0 (unless specified otherwise), supplemented with different concentrations of KCl). Following incubation for 2 min at 30°C, the transport reaction was initiated by the addition of [ 14 C]glycine betaine (Amersham Biosciences) to a final concentration of 31 M (more than 10-fold above the K m for transport and K D for binding) (13). At given time intervals, 40-l samples were taken and diluted with 2 ml of ice-cold isotonic assay buffer.…”
Section: Transport Assaysmentioning
confidence: 99%